THE EFFECTIVENESS OF DIGITAL TECHNOLOGIES IN TEACHING ENGLISH: A COMPARISON OF ONLINE PLATFORMS AND TRADITIONAL METHODS - Ibragimova , Dilnoza (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
This article examines the effectiveness of digital technologies in teaching English, with a particular focus on comparing online learning platforms and traditional teaching methods. The rapid development of information and communication technologies has transformed the field of education, creating new opportunities for interactive, individualized, and flexible language learning. At the same time, traditional methods, which emphasize face-to-face interaction and communicative competence, remain highly valuable. By analyzing both approaches, the study highlights their advantages, limitations, and the potential for integration. The findings suggest that the most effective strategy is a blended approach that combines the flexibility and accessibility of digital platforms with the communicative strengths of traditional classroom practices.